2009
DOI: 10.1084/jem.20091508
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of autoimmune demyelination by the inhibitory receptor CLM-1

Abstract: Multiple sclerosis and its preclinical model, experimental autoimmune encephalomyelitis, are marked by perivascular inflammation and demyelination. Myeloid cells, derived from circulating progenitors, are a prominent component of the inflammatory infiltrate and are believed to directly contribute to demyelination and axonal damage. How the cytotoxic activity of these myeloid cells is regulated is poorly understood. We identify CMRF-35–like molecule-1 (CLM-1) as a negative regulator of autoimmune demyelination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 26 publications
3
71
2
Order By: Relevance
“…16,19,26 In agreement with this findings, blocking of CD300a and PS interactions induces increased inflammatory cytokine production from mast cells, 26 and CD300f deficiency leads to a predispostion to autoimmune disease development, 19 as well as an exacerbation in the allergic responses and autoimmune diseases. 19,25,33,34 In contrast, our data characterize CD300b as a positive regulator of phagocytosis, through its association with DAP12. The exact role of CD300b in efferocytosis remains to be elucidated, but the existing data suggest that CD300b is involved in the regulation of some immune responses.…”
Section: Resultscontrasting
confidence: 67%
“…16,19,26 In agreement with this findings, blocking of CD300a and PS interactions induces increased inflammatory cytokine production from mast cells, 26 and CD300f deficiency leads to a predispostion to autoimmune disease development, 19 as well as an exacerbation in the allergic responses and autoimmune diseases. 19,25,33,34 In contrast, our data characterize CD300b as a positive regulator of phagocytosis, through its association with DAP12. The exact role of CD300b in efferocytosis remains to be elucidated, but the existing data suggest that CD300b is involved in the regulation of some immune responses.…”
Section: Resultscontrasting
confidence: 67%
“…55 Besides the SLE-like disease as shown in this study, CD300f deficiency has been shown to contribute to development and pathogenesis of experimental autoimmune encephalomyelitis and colitis in mouse models. 56,57 An intronic SNP (rs10512597) of CD300f has been associated with the etiology of psoriasis disease and possibly with cardiovascular diseases. 58,59 A nonsynonymous SNP (rs2034310) in the region encoding the cytoplasmic part of CD300f has been associated with multiple sclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…51 However, these results were not reproduced by others. 77 In another study, it was shown that mouse CD300f-Fc binds to apoptotic cells, suggesting that CD300f also recognizes phospholipids exposed on the outer leaflet of the plasma membrane of dead cells. Indeed, this binding was blocked when the PS ligand annexin V was present in the assay.…”
Section: 76mentioning
confidence: 99%